E-Wallet dalam Rutinitas: dari Gaya Hidup Praktis Hingga Risiko Digital - Ernisa, Putri; Pratiwi, Cindy Aulia; Trinanda, Lia; Putri Apandi, Khairnadila (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to understand e-wallet usage patterns in everyday life and assess the benefits and risks perceived by users. The study subjects consisted of individuals of various ages and occupations who actively use e-wallets. Data collection was conducted through an online survey using Google Forms, with 61 respondents obtained through snowball sampling. Data analysis was conducted quantitatively and descriptively by calculating percentages to identify trends and usage patterns. The results show that the majority of users are women aged 18–23, with the DANA app being the most commonly used platform. The most popular features are cashback and QR scanning due to their convenience and practicality. Risks such as loss of funds are relatively low, although concerns remain regarding the security of personal data. Therefore, user education and protection need to be continuously improved.